2018
DOI: 10.1089/aivt.2017.0020
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Mitigates the Negative Effects of Arsenic Contamination in anIn VitroWound Model

Abstract: Arsenic, a naturally occurring environmental contaminant, is harmful to humans at elevated concentrations. Increased levels of arsenic in the environment occur as a result of human activities and from natural geologically sourced leaching into ground and surface water. These sources pose an exposure risk above the USEPA standard to individuals whose food and water sources become contaminated. Arsenic exposure negatively impacts organ function and increases the risk for developing pathologies, including cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Rippon et al, 2016 demonstrated a counter-intuitive model about healing wounds using the "hyper-hydration" of tissue, in which tissue is hydrated beyond the normally acceptable therapeutic level. Another study has reported that hydrotherapy provides an optimal healing environment through autolytic debridement and absorption of wound fluid, which enables re-epithelialization to occur in an unrestricted fashion (Pinto et al, 2018;Lin et al, 2017). However, in this work, Zamzam water showed potent wound healing properties, which may be due to the presence of a trace level of many minerals.…”
Section: Wound Healing Propertiesmentioning
confidence: 66%
“…Rippon et al, 2016 demonstrated a counter-intuitive model about healing wounds using the "hyper-hydration" of tissue, in which tissue is hydrated beyond the normally acceptable therapeutic level. Another study has reported that hydrotherapy provides an optimal healing environment through autolytic debridement and absorption of wound fluid, which enables re-epithelialization to occur in an unrestricted fashion (Pinto et al, 2018;Lin et al, 2017). However, in this work, Zamzam water showed potent wound healing properties, which may be due to the presence of a trace level of many minerals.…”
Section: Wound Healing Propertiesmentioning
confidence: 66%
“…Application of this assay provides a high-throughput and timely evaluation of cellular migration and may directly translate to complex physiological systems 5,6,7 . For this reason, the proposed bench-top model has been tuned and practiced to evaluate the effects of various therapeutic agents and environmental toxins on wound healing…”
Section: Discussionmentioning
confidence: 99%
“…. Another common technique, described in this study, is the use of inverted light microscopy with phase contrast 6,7 . This alternative to cell dyes and fluorescence allows the user to live track cells without having to terminally fix cells prior to imaging and also allows for capturing images of the same individual wells containing wounded monolayers of cells across time points.…”
mentioning
confidence: 99%
“…Wound healing assay was performed according to the method of Pinto and Ramenzoni with modification (Pinto BI et al, 2018, Ramenzoni et al, 2017. The CL-6 cells (1.0×10 4 cell/well) were seeded onto a 96-well plate and incubated overnight at 37 o C under 5% CO 2 atmosphere.…”
Section: Wound Healing Assaymentioning
confidence: 99%